Chromosomal Rearrangement and Loss of Heterozygosity in Cervical Cancer Amongst Patients in Hospital Kuala Lumpur - Ismail, Siti Norlasiah (2004)
Cervical carcinoma is the second most common malignancy among women worldwide. The highest incidence rates are observed in developing countries. The susceptibility to cervical carcinoma in high incidence populations may result from several factors including human papillomavirus (HPV) exposure and both inherited and acquired genes. HPV infection does not always led to cervical cancer. In cervical carcinoma the other common genetic characteristic of cancer is the presence of several recurrent genetic alterations, not related to HPV. The type of recurrent genetic damage might take different forms such as gene amplification, chromosomal translocation, deletions, loss of heterozygosity, point mutation, transcriptional silencing, and in some tumors viral DNA integration. To deter-mine the possible genetic alterations amongst the Malaysian women with cervical cancer, this study was conducted on 50 cervical tumor biopsies received from the Department of Obstetrics and Gynecology of the Hospital Kuala Lumpur. The objectives of the study were; i) the establishment of short-term primary cell culture of human cervical epithelial cells derived from cervical tumors for the determination of the prevalence and the type of chromosomal aberrations, ii) characterization of the allelic losses of the chromosomes 3p, 5p, 11 and 17p (p53), subsequently identification of a possible site of candidate tumor suppressor gene(s) and iii) to determine the HPV status of the cervical cancers. Primary cell culture and cytogenetic techniques were performed on the cervical tumor biopsies. G-banding was employed for the identification of the chromosomes. To define the localization of the tumor suppressor genes, loss of heterozygosity study was performed on 37 cervical cancer cells. Twenty-four microsatellite polymorphic markers for the chromosomes 3p, 5p, 11 and p53 were chosen, the normal and tumor DNAs from each patient were analyzed for the allelic loss using PCR-based microsatellite analysis. The status for HPV 16 E6 and HPV 18 E6 was detected by PCR method. Twenty-five cervical cancer biopsies were successfully karyotyped and near-diploid was the modal number, with a majority of them being hypodiploid (35-45). About 50% of the metaphases obtained in the 25 tumors were hypodiploids, 12.1% were hyperdiploids, and 36.7% were diploids. Numerical abnormalities were predominantly observed in the patients, with monosomies of chromosomes 17, 22, X, 1 1, 18, 19, 13, and 6. Fluorescence in situ hybridization using centromeric probes 1 1, 17 and 18 confirmed the presence of monosornies 1 1, 17, 18 in a low percentage, 12.0%. 16.2% and 26.4% respectively. Several clones of cells were observed, with possibility of 45,)(X,-22; 45,XX.-11; 45,=,- 19 and 45,XX.- 18. Twenty-six of the 36 informative individuals exhibited LOH at one locus or more. The highest incidence was observed in chromosome 3p with the frequency of 48.6%. while a low frequency of 2.7% was detected in the short-arm of chromosome 17 at position 17~13.1w, hereby lies the p53 tumor suppressor. LOH was confined to four prominent regions, 1 1q23.3, 3p 14.2-3p 14.1, 3p2 1.32 and 3p25.3- 3p25.1. No signiacant correlation was found between the LOH and the grade of cancer differentiation. The difference between the LOH frequency in cervical carcinomas with early stage and those with advanced stage was not statistically si@icant. Only 5 1.4% of the 35 tumors were positive for HPV 16 E6 and 17.2% was HPV 18 E6 positive. HPV 16 was found to be positive in 64.7% of the Chinese, 41.7% in Malays and 50% in the Indians. Both the Malays and the Indians were observed to harbor the HPV 18 at a higher frequency (40 and 33.3% respectively) than the Chinese. In conclusion, besides HPV infection, other genetic abnormalities play a role in cervical carcinogenesis. LOH is a better method than chromosomal analysis in searching for possible tumor suppressor gene(s) that is responsible for c e ~ c atlu morigenesis. Mapping of the smallest region of LOH in these tumors and analysis of candidate genes present in the region of LOH will be continued.